2011
DOI: 10.1146/annurev-pathol-011110-130303
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids, Retinoic Acid Receptors, and Cancer

Abstract: Retinoids (i.e., vitamin A, all-trans retinoic acid, and related signaling molecules) induce the differentiation of various types of stem cells. Nuclear retinoic acid receptors mediate most but not all of the effects of retinoids. Retinoid signaling is often compromised early in carcinogenesis, which suggests that a reduction in retinoid signaling may be required for tumor development. Retinoids interact with other signaling pathways, including estrogen signaling in breast cancer. Retinoids are used to treat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
501
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 520 publications
(507 citation statements)
references
References 137 publications
5
501
0
1
Order By: Relevance
“…[13][14][15] Retinoids are among the most effective pro-differentiating molecules and have been proposed as anticancer agents. 16 Interestingly, it has been shown that all-trans retinoic acid (RA), by inhibiting the activator protein-1, reduces MS formation and the expression of IL6. 17 In inflamed human chondrocytes, retinoids hamper the expression of nitric oxide synthase, cyclooxygenase-2 and of various chemokines, 18 thus leading to argue in favor of their anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Retinoids are among the most effective pro-differentiating molecules and have been proposed as anticancer agents. 16 Interestingly, it has been shown that all-trans retinoic acid (RA), by inhibiting the activator protein-1, reduces MS formation and the expression of IL6. 17 In inflamed human chondrocytes, retinoids hamper the expression of nitric oxide synthase, cyclooxygenase-2 and of various chemokines, 18 thus leading to argue in favor of their anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism for the repression of endogenous CYP26A1 expression by 3 days ATRA treatment could not be explained clearly in this point. Retinoid treatment might suppress cancers of many tissues including lung tumor and ATRA, as the most active form of RA, is currently used as a chemotherapy drug [19,28]. It is also known that ATRA is involved in the process of programmed cell death (also known as apoptosis) in certain types of tumor cells [21,33].…”
Section: Regulation Of Cyp26a1 Gene Expression By Atra In the Mtcc Cellsmentioning
confidence: 99%
“…In this context, the so-call differentiation therapy is now widely studied. Retinoic acid (RA, Vitamin A), for example, is one of the most thoroughly studied drugs that are capable of inducing CSC differentiation (Sell 2004;Tang and Gudas 2011;Gudas and Wagner 2011). However, mainly due to retinoid resistance and some serious side effects, the clinical outcome of RA treatment is not satisfactory for many solid tumors (Sell 2004).…”
Section: The Evolving Concept Of the Cancer Stem Cell Modelmentioning
confidence: 99%